Cross-cultural communication : do Icelanders have the proficiency to communicate effectively across cultures?: the position of cross-cultural curricula and training in Iceland and possible remedial action - Steinunn Aðalbjarnardóttir (2005)
The object of this assignment is to reason the importance of intercultural competence, find out the position of cross-cultural education and training in Iceland and finally discuss remedial actions. The part of culture that usually causes the most misunderstanding and confusion in cross-cultural communication is the hidden part of it such as values, norms, assumptions and attitudes. Hofstede´s dimensions are useful when communicating with a country that has been placed in the indices of Power distance, Individualism/ Collectivism, Masculinity/Femininity, Uncertainty avoidance and Long-term / Short-term orientation. As well are the seven dimensions of Trompenaars, which focus on the cultural dimensions of business executives and are related to how a group of people solve problems and reconciles dilemmas. Adjusting to a new culture can be an extremely difficult task causing irritation, frustration and anxiety because of endless cultural misunderstanding (Culture shock). Language can be considered the vehicle of culture whereas language and culture are closely interwoven. There is a rapid growth in cultural related courses both in under- and postgraduate in Business fields even though the emphasis is more on geographic areas or international relations and less with cross-cultural communication. There are as well many students studying abroad under the auspice of the universities. The results of a survey conducted among language teachers in the colleges indicate that the teachers are very culturally aware and motivated for discussing cultural issues such as values, behaviour and assumptions with their students even though almost no teacher had heard of Hofstede. The Trade Council of Iceland has responded to the need of the business sector by training cross-cultural consultants and involving cultural topics into their seminars. The International Centres play a vital part in the cultural education for immigrants whose number is rapidly increasing in Iceland. The general education system is just starting to respond to ...